2014
DOI: 10.1371/journal.pone.0114924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Randomized Intervention to Improve Workplace Social Capital in Community Health Centers in China

Abstract: ObjectiveTo examine whether workplace social capital improved after implementing a workplace social capital intervention in community health centers in China.MethodsThis study was conducted in 20 community health centers of similar size in Jinan of China during 2012–2013. Using the stratified site randomization, 10 centers were randomized into the intervention group; one center was excluded due to leadership change in final analyses. The baseline survey including 447 staff (response rate: 93.1%) was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Update searches (Oct 2013 and Sept 2016) identified a further 7 studies (6 from update searches and 1 from hand searching). A total of eleven studies [ 6 , 23 32 ] were included, and are summarised in Tables 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Update searches (Oct 2013 and Sept 2016) identified a further 7 studies (6 from update searches and 1 from hand searching). A total of eleven studies [ 6 , 23 32 ] were included, and are summarised in Tables 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
“…All reviewed studies included self-reported measures of individual health behaviours and health outcomes, and four studies [ 6 , 23 , 28 , 29 ] included self-reported measures of the psychosocial workplace environment (see Table 3 ). Two studies [ 28 , 32 ] reported Body Mass Index (BMI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested associations between workplace social capital and mental health [ 27 , 28 ]. However, only a few studies have suggested how to elevate workplace social capital [ 29 , 30 ]. An elevation of acceptance of selfishness at the workplace followed by an elevation of Maslow’s synergy may elevate workplace social capital.…”
Section: Discussionmentioning
confidence: 99%